Research on Optimization Strategies for the Resilience of Grass-roots Grid Governance in Complex Risk Environments - Guo, Suhui (Transactions on Economics, Business and Management Research, 2024)
Under the complex risk environment, grass-roots grid governance has the problems of over-administrative service process, tendency of introducing technology to be performative, the subject power is always single, and the structure system is in weightlessness. In order to enhance the resilience of grass-roots grid governance, the status of grass-roots grid governance should be clarified, the content of grass-roots grid governance should be controlled, the form of grass-roots grid governance should be shaped, and the norms of grass-roots grid governance should be formulated. In governance, the administrative authorities should pull in multiple forces, lay a good foundation for grass-roots grid governance, use modern technology to enhance resilience, improve grass-roots grid supervision, introduce technical talent, ensure the effectiveness of grass-roots grid governance, reduce administrative intervention, and improve the power of grass-roots grid autonomy.